In Situ Silver‐Based Electrochemical Oncolytic Bioreactor. Issue 40 (4th September 2022) - Huang, Yong; Zhong, Liping; Li, Xiaotong; Wu, Pan; He, Jian; Tang, Chao; Tang, Zhiping; Su, Jing; Feng, Zhenbo; Wang, Bing; Ma, Yun; Peng, Hongmei; et al.
Abstract: In this study, it is shown for the first time that a reduced graphene oxide (rGO) carrier has a 20‐fold higher catalysis rate than graphene oxide in Ag + reduction. Based on this, a tumor microenvironment‐enabled in situ silver‐based electrochemical oncolytic bioreactor (SEOB) which switched Ag + prodrugs into in situ therapeutic silver nanoparticles with and above 95% transition rate is constructed to inhibit the growths of various tumors. In this SEOB‐enabled intratumoral nanosynthetic medicine, intratumoral H2 O2 and rGO act as the reductant and the catalyst, respectively. Chelation of aptamers to the SEOB‐unlocked prodrugs increases the production of silver nanoparticles in tumor cells, especially in the presence of Vitamin C, which is broken down in tumor cells to supply massive amounts of H2 O2 . Consequently, apoptosis and pyroptosis are induced to cooperatively contribute to the considerably‐elevated anti‐tumor effects on subcutaneous HepG2 and A549 tumors and orthotopic implanted HepG2 tumors in livers of nude mice. The specific aptamer targeting and intratumoral silver nanoparticle production guarantee excellent biosafety since it fails to elicit tissue damages in monkeys, which greatly increases the clinical translation potential of the SEOB system. Abstract : A tumor microenvironment‐enabled in situ silver‐based electrochemical oncolytic bioreactor has been established to unlock anti‐tumor Ag + prodrugs for highly‐efficient subcutaneous and orthotopic tumor recession via activating reactive oxygen species production, wherein reduced graphene oxide featuring 20‐fold larger catalysis rate than graphene oxide allows intratumoral H2 O2 as reductants to reduce Ag + into silver nanoparticles especially after uniting with VitC‐mediated H2 O2 production.